Cultural Wisdom and Social Values in the Sondlah Tradition: A Reflection of Local Identity in Sundanese Culture - Desi qoriah; Dioka Muhammad Akbar; Mutiana Nurmalasari; Muhamad Hilman Firmansyah (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2026)
This study investigates the cultural wisdom and social values embodied in the traditional Sundanese game Sondlah as a reflection of local identity. The main problem addressed is how symbols and linguistic expressions within the game convey moral and philosophical meanings in Sundanese culture. Using a qualitative analytical method that integrates semiotic and ethnolinguistic approaches, data were obtained through literature review, observation, and interviews with local cultural practitioners. The semiotic analysis interprets movement, spatial design, and game objects as symbolic signs representing life balance, discipline, and human intention, while the ethnolinguistic analysis reveals linguistic expressions such as hampura (sorry) and ulah pegat (don’t break it) as manifestations of humility, respect, and social harmony. The findings show that Sondlah functions as a living medium of cultural transmission and moral education, integrating physical, verbal, and philosophical dimensions of Sundanese identity. The study concludes that Sondlah embodies the philosophy of hirup sauyunan “living in harmony” and continues to serve as a dynamic cultural code preserving local wisdom in modern society.